2022
DOI: 10.1038/s41598-022-09922-2
|View full text |Cite
|
Sign up to set email alerts
|

Evoked responses to rhythmic visual stimulation vary across sources of intrinsic alpha activity in humans

Abstract: Rhythmic flickering visual stimulation produces steady-state visually evoked potentials (SSVEPs) in electroencephalogram (EEG) recordings. Based on electrode-level analyses, two dichotomous models of the underpinning mechanisms leading to SSVEP generation have been proposed: entrainment or superposition, i.e., phase-alignment or independence of endogenous brain oscillations from flicker-induced oscillations, respectively. Electrode-level analyses, however, represent an averaged view of underlying ‘source-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(62 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, the lateral parietal region showed the most consistent relative harmonic phase, which was significantly non-uniform up to the sixth harmonic. Our finding of a distinct parietal alpha rhythm accords well with previous findings suggesting that parietal and occipital alpha oscillations may represent functionally distinct rhythms (Barzegaran et al, 2017;Haegens et al, 2014;Nuttall et al, 2022;Sokoliuk et al, 2019).…”
Section: Additional Parietal Alpha Waveformssupporting
confidence: 92%
“…Furthermore, the lateral parietal region showed the most consistent relative harmonic phase, which was significantly non-uniform up to the sixth harmonic. Our finding of a distinct parietal alpha rhythm accords well with previous findings suggesting that parietal and occipital alpha oscillations may represent functionally distinct rhythms (Barzegaran et al, 2017;Haegens et al, 2014;Nuttall et al, 2022;Sokoliuk et al, 2019).…”
Section: Additional Parietal Alpha Waveformssupporting
confidence: 92%
“…Event-related alpha desynchronization during visual processes has been previously reported (Pfurtscheller et al, 1994 ; Suffczynski et al, 2001 ), which might have implications for the responses in that range. Variation in evoked responses to flicker across sources of endogenous alpha oscillatory activity has also been observed (Nuttall et al, 2022 ). In our previous research (Tsoneva et al, 2015 ), we also noted several distinct evoked patterns in delta (1–4 Hz), theta (4–8 Hz), alpha (8-12 Hz) and beta (15-30 Hz) bands, which could contribute to the SSVEP response measured at those frequencies.…”
Section: Discussionmentioning
confidence: 94%
“…In this light, it should be considered that other mechanisms can also contribute to oscillatory activity, such as the superposition of event-related responses, which are evoked cortical responses to visual stimulation that add onto, but do not interact with, ongoing oscillations [48]. Moreover, a recent study using rhythmic flickering checkerboards found evidence for both frequency-specific neural responses, supporting the entrainment model, and frequency-independent resonance phenomena, supporting the superposition model [49]. As we found that intensity of FLS effects was affected by frequency, it is likely that underlying frequency-specific neural responses, such as entrainment, contribute to FLS effects.…”
Section: Potential Underlying Neural Mechanismsmentioning
confidence: 89%